ANALISIS FAKTOR MOTIVASI, LINGKUGAN KERJA, DISIPLIN DAN PENGARUHNYA TERHADAP KINERJA GURU HONORER DI KABUPATEN TANGERANG - Tri Endi Ardiansyah PS; Abella Sistra P (Universitas Muhammadiyah Tangerang, 2019)
This research aimed to analys factors motivation, work-environment,discipline and its impact to work-performance of part-time teacher inregion Tangerang. There are some assumptions in around thecondidition, one of them is compensation package that below than basicsalary standrard. Beside it, there are some assumes tht value andamount wil equel to quality, performance and spirit to motivate ofteachers. As pre-assumption, motivation of teacher was had tocontribute for assesment of professional performance of teacher andfinally will point to wages and teachers welfare. In this research,analysis technique by using multi-rergession analysis, hypothesis analysisby using t-test and f-test. In additional, this research using classicalassumptiontest where include normality test, auto-correlation test,hetereo-schedashticity, multi-coliniearity test. The result of researchshown that motivation, work-environtment and discipline have significantimpact to work-performance of teacher.